2003
DOI: 10.1034/j.1600-0692.2003.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory flow in the steelmaking vessel

Abstract: Physical modelling of the basic oxygen furnace (BOF) was undertaken with the object of developing an overall flow pattern within the vessel as a function of fluid-flow dynamics/vessel geometry interaction. The study was initiated as the result of localised refractory wear occurring in the knuckle region of a BOF vessel. The occurrence of the wear coincided with a change in lance tip design. This preferential wear limited the campaign life of the vessel. Modelling the fluid dynamics of the system was to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…(12). This is consistent with the finding by Lee et al (2003), where the wave motion was constant and only dependent on the vessel size when the liquid height or submerged depth is large enough. Since the sloshing wave becomes stable quickly, less than 4 s as shown in Fig.…”
Section: Surface Sloshingsupporting
confidence: 92%
“…(12). This is consistent with the finding by Lee et al (2003), where the wave motion was constant and only dependent on the vessel size when the liquid height or submerged depth is large enough. Since the sloshing wave becomes stable quickly, less than 4 s as shown in Fig.…”
Section: Surface Sloshingsupporting
confidence: 92%
“…In addition, the slag surface is not stable, and the propagation of surface waves on the slag surface formed during the oxygen impact on molten pool aggravates the instability of the slag surface. [24] Investigation of the coverage area of the slag phase is the key to elucidate the influence of the swirl angle on the gas-slag-metal behavior. The variation in the coverage area of the slag phase of different nozzle-twisted lances with the blowing time is shown in Figure 6.…”
Section: Characteristics Of the Interfacementioning
confidence: 99%
“…In this study, the impact zone is defined as the smooth surface of the cavities formed by the supersonic jets from the lance, where the oxygen comes in contact with the metal bath. Previous studies [61][62][63][64] indicated that the cavity surface is rough, resulting in the generation of "splash sheets" [64] or "metal-bath spraying effect" [61]. However, the surface area enhancement due to splash sheet formation is difficult to estimate.…”
Section: Determination Of Impact (Reaction) Areamentioning
confidence: 99%